From urban core to wealthy towns: Nonschool fiscal disparities across Connecticut municipalities - Bo Zhao (Federal Reserve Bank of Boston, 2015)
Using a cost-capacity gap framework, this paper is the first study to quantify nonschool fiscal disparities across Connecticut municipalities. In the absence of a Uniform Chart of Accounts for municipalities, the paper uses a newly assembled dataset of multi-year local financial records, adjusted to be comparable across municipalities and therefore suitable for regression analysis. The paper finds significant nonschool fiscal disparities among Connecticut municipalities. Fiscal disparities are driven primarily by the uneven distribution of the property tax base across the state, while cost differentials also play an important role. State nonschool grants are found to have a relatively small effect in offsetting municipal fiscal disparities. Unlike previous research focused on a single state, this paper also conducts a comparison between Connecticut and Massachusetts. This paper's conceptual framework and empirical approach are generalizable to other states.
Keywords: H70; H71; H72; H73; H77; H83; H20; 330; fiscal disparities; municipal gap; municipal cost; revenue-raising capacity; property tax; state grants